2001
DOI: 10.1002/ajh.1179
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of platelet transfusions after plasma exchange in adult thrombotic thrombocytopenic purpura: A report of two cases

Abstract: Plasma infusion (PI) and plasma exchange (PE) are the most efficient treatment of thrombotic thrombocytopenic purpura (TTP), allowing achievement of complete remission in 60 to 90% of cases. Life‐threatening bleeding, related to severe thrombocytopenia, is one of the main complications of the disease. Thrombocytopenia may also preclude invasive procedures such as splenectomy, which may be required during the management of TTP. Platelet concentrates transfusions are usually thought to worsen the disease, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…Most of the patients reviewed received plasma exchange at the time of transfusion. Our findings are similar to several other case studies which reported no worsening in clinical status or mortality in patients who received platelet transfusion while also receiving treatment for TTP with plasma exchange [7][8][9][10]. One of the largest studies, done by Swisher and colleagues, was a prospective cohort looking at 54 patients with TTP from the Oklahoma TTP-HUS registry, 33 of whom received platelet transfusion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of the patients reviewed received plasma exchange at the time of transfusion. Our findings are similar to several other case studies which reported no worsening in clinical status or mortality in patients who received platelet transfusion while also receiving treatment for TTP with plasma exchange [7][8][9][10]. One of the largest studies, done by Swisher and colleagues, was a prospective cohort looking at 54 patients with TTP from the Oklahoma TTP-HUS registry, 33 of whom received platelet transfusion.…”
Section: Discussionsupporting
confidence: 93%
“…These recommendations are based on a small number of case reports describing worsening neurologic outcomes or mortality within hours of platelet transfusion; however, the patients in these reports did not receive plasma exchange prior to or during platelet transfusion [2][3][4][5][6]. Some recent studies, however, have described no adverse outcomes in patients with TTP who received platelet transfusion [7][8][9][10].…”
Section: Introductionmentioning
confidence: 96%
“…As suggested by other groups who challenged the harm from PLT transfusions in patients with TTP, PLT infusion may be safely proposed in patients with TTP who require a surgical procedure to limit bleeding complications 34 . In this context, the concomitant use of TPE may reduce the risk of adverse effects associated with PLT infusions 35 …”
Section: Discussionmentioning
confidence: 99%
“…Early complications of platelet transfusions given to patients with TTP resulted in the recommendation to avoid this treatment except for life-threatening bleeding [36]. However, a recent review of the Oklahoma TTP-HUS Registry, based on 382 consecutive patients, concluded that the evidence that platelet transfusions are harmful for patients with TTP is uncertain [30,37], in particular, if given simultaneously with the plasma exchange therapy [37,38]. Thus, all children with hematological complications of HIV and questionable adherence to ART need to be monitored closely as TMA lesions can develop in a relatively short period of time.…”
Section: Discussionmentioning
confidence: 99%